Relationship between Spinal Anesthesia and Hypothermia Incidence among Post Operative Patients in the Operating Recovery Room "JIH" Hospital Yogyakarta - Maryudella Afrida; Erika Nurwidiyanti; Marfuah Marfuah (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Complications of surgery may lead the patient to experience ill and even death. One of the complications in the patient after surgery with spinal anesthesia is the incidence of hypothermia. Hypothermia can occur as a result of a combination of anesthesia and surgery that causes disturbance in body temperature regulation that can make decreasing body temperature. Method: This research uses a descriptive correlational method with a retrospective approach, with total sampling technique amount of 106 respondents, using a checklist sheet research instrument.Data analysis techniques spearman rank. Results: The characteristics of surgery patients with spinal anesthesia in the operating room of Yogyakarta "JIH" Hospital were mostly female, 87.9%, most of whom were adults 74.1%, the highest frequency of surgery with spinal anesthesia duration >2 hours 55.7% and had an incidence of hypothermia 54.7%. Correlational statistical analysis obtained a Cramer's value of 0.371, a correlation coefficient value of 0.348 with a probability value (p-value) of 0.000. Conclusion: There is a relationship between spinal anesthesia and hypothermia incidence among postoperative patients in the operating recovery room "JIH" Hospital Yogyakarta. The direction of the correlation is positive and closeness is sufficient.